PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP KEPERCAYAAN DIRI MAHASISWA - Rosidah, Noneng Siti; Rahman, Imas Kania; Faizah, Tya Amiratul; Hamidah, Rizka Nur (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
Students are in a transitional phase of adolescent development towards early adulthood. In the process of fulfilling their developmental tasks, of course many things are gone through and require individual adjustments. Individual success in adjusting to a new environment or activity, one of the major assets is self-confidence. Self-confidence can be developed through guidance and counseling services. Therefore, this study aims to analyze whether there is an influence of group guidance services on students' self-confidence based on differences in gender between men and women. The research method used is quantitative descriptive. The data collection method uses observation, questionnaires and documentation. The data analysis technique uses statistical regression test analysis. The results of the study showed that the F count was 2.738 with an F table value of 4.183 of 2.738 <4.183, so there is no influence of the group guidance variable on the self-confidence variable. Likewise, the results of the statistical analysis between men and women showed no significant difference in group guidance services on students' self-confidence. Because the level of student confidence is in the medium and high categories, it is necessary to provide other guidance and counseling services in order to increase the self-confidence of students in the medium to high categories. So it is necessary to plan programs or service topics that are relevant and representative of the current needs of individuals. Abstrak Mahasiswa berada pada masa peralihan fase perkembangan remaja menuju dewasa awal. Dalam proses memenuhi tugas perkembangannya, tentu banyak hal yang dilalui dan butuh penyesuaian individu. keberhasilan individu dalam penyesuaian diri dengan lingkungan atau aktivitas baru salah satu modal besarnya adalah kepercayaan diri. Kepercayaan diri salah satunya dapat dikembangkan melalui layanan bimbingan dan konseling. Oleh karena itu penelitian ini bertujuan untuk menganalisis apakah terdapat pengaruh dari layanan bimbingan kelompok terhadap kepercayaan diri mahasiswa ditinjau berdasarkan perbedaan jenis kelamin laki-laki dan perempuan. Metode penelitian yang digunakan adalah kuantitatif deskriptif. Metode pengumpulan data menggunakan observasi, angket dan dokumentasi. Teknik analisis data menggunakan analisis uji statistik regresi. Hasil penelitian menunjukkan bahwa diperoleh F hitung sebesar 2,738 dengan nilai F tabel sebesar 4,183 sebesar 2,738 < 4,183, maka tidak terdapat pengaruh variabel bimbingan kelompok terhadap variabel kepercayaan diri. Begitu pula hasil analisis statistik antara laki-laki dan perempuan menunjukkan tidak adanya perbedaan yang signifikan dalam layanan bimbingan kelompok terhadap kepercayaan diri mahasiswa. Karena tingkat kepercayaan mahasiswa berada pada kategori sedang dan tinggi, maka perlu diberikan layanan bimbingan dan konseling lainnya agar dapat meningkatkan kepercayaan diri mahasiswa pada kategori sedang menjadi tinggi. Sehingga perlu direncanakan program atau topik layanan yang relevan dan representatif dengan kebutuhan individu saat ini.